(untitled) (Journal of Plant Disease Sciences, 2024)
Chilli hybrids are demonstrated in farmers’ fields of Hadagali and Arakeri blocks of Vijayapura district on nearly 50ha area,for the year 2019-20 and 2020-21 under on farm testing trials. Arka Kyati, Arka Meghana and local variety were used in this study. Arka Kyati recorded highest growth characters like plant height (47.24 cm), number of fruits/plant (78.30), fruit weight (5.31 g) and fruit length (10.19 cm) followed by Arka Meghana with 48.54cm; 67.50; 5.20g and 10.10 cm, respectively, whereas local hybrid recorded the lowest values for all the traits. Arka Kyati took the minimum number of days for 50 per cent flowering (43). Arka Kyati hybrid recorded the highest per plantyield (413.00 g) and total yield/ha (15.47 t/ha) followed by Arka Meghana (388.90 g; 13.26 t/ha). Arka Kyati recorded lowest thrips and Powdery mildew incidence (16.25% and 7.89%) whereaslocal checkrecordedthe lowest yield of 11.98 t/ha and highest thrips and powdery mildew incidence (20.36% and 13.28%). In the case of benefit cost ratio, Arka Kyati recorded the highest B:C ratio of2.37 with the net profit of Rs. 1,89,616. Arka Kyati hybrid is performed well and increasedyieldof 17.30 per cent.